Pola Asuh Pada Keluarga Yang Memiliki Anak-Anak Penyandang Disabilitas Intelektual Di Kelurahan Samata Kecamatan Somba Opu, Kabupaten Gowa - Mubarak, Muhammad Fahmi; Subardhini, Meiti; Ardiyantika, Sulistyary (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Parenting is a form of interaction or a picture of parental attitudes and behaviour towards children by giving attention to children and providing direction so that children can achieve the things they want or achieve their developmental tasks. This study used a qualitative approach with in-depth interviews, observation, and documentation studies. The determination of data sources in this study was carried out using a census sampling technique (saturated sampling). The purpose of this study was to determine the form of family parenting in the aspects of supervision or control, communication, and disciplining children with intellectual disabilities in Samata Village, Somba Opu District. The family parenting style for children with intellectual disabilities is quite good in terms of supervision and control. However, the family experienced obstacles in the aspects of communication and discipline. Parents find it difficult to build communication with children with intellectual disabilities because of the condition of children with intellectual disabilities who stammer when speaking and are not even able to speak. In the disciplinary aspect, two informants did not carry out disciplinary action because they were confused about applying schedules and rules to children with intellectual disabilities so that it was often seen that children with intellectual disabilities behaved according to good or their wish. Referring to these problems, the researcher proposes a program to increase family knowledge and skills in implementing it Good Parenting to children with intellectual disabilities through Educational Group.